2015
DOI: 10.1007/s12161-015-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pretreatment Method for Determination of Nisins A and Z and Monitoring in Cheese Using Liquid Chromatrography-Tandem Mass Spectrometry

Abstract: The peptide nisin produced by Lactococcus lactis subsp. lactis is known to be one of the natural preservatives that are used in various foods including cheese products. This study optimized and validated a liquid chromatographytandem mass spectrometry method for determining nisin A and nisin Z in cheese. Processed and natural cheeses were used for method validation. In addition, this study investigated the content of nisin A and nisin Z in 140 cheese samples comprised of imported and domestic cheese. The nisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…These differences are in agreement with other studies on the stability of nisin in broth or foods after heat treatments(Davies et al, 1998). For instance,Schneider et al (2011) found the nisin A concentrations determined by LC-MS/MS in processed cheese to be reduced more than 92 % by a heat treatment at 120°C during 30 min Ko et al (2016). also quantified low nisin A concentrations in processed cheese by LC-MS/MS (0.34-0.64 mg/kg) but no information on nisin A concentrations recipes were provided.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These differences are in agreement with other studies on the stability of nisin in broth or foods after heat treatments(Davies et al, 1998). For instance,Schneider et al (2011) found the nisin A concentrations determined by LC-MS/MS in processed cheese to be reduced more than 92 % by a heat treatment at 120°C during 30 min Ko et al (2016). also quantified low nisin A concentrations in processed cheese by LC-MS/MS (0.34-0.64 mg/kg) but no information on nisin A concentrations recipes were provided.…”
supporting
confidence: 91%
“…MS/MS method developed in the present study provided recovery values similar to those previously obtained byKo et al (2016); however the present study used an extraction solvent without NaCl as it can interfere with ionization, cause ion suppression and broader peaks in the LC-MS/MS(Sterling et al, 2010). Residual concentrations of nisin A quantified in the present study using LC-MS/MS (0.56-5.28 ppm) were lower than the added concentrations used in the cheese formulations (11.2-12.0 ppm).…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Thus, the EC/ECL dual-modality sensing platform for the highly sensitive determination of nisin is established for the first time. Comparison between determination of nisin using different strategies is demonstrated in Supplementary Table S1 (SI) ( 14 , 17 , 52 54 ). The LOD obtained by EC detection is lower than that obtained from micellar electrokinetic chromatography (MEKC) ( 54 ), liquid chromatography-mass spectrophotometry/mass spectrophotometry (LC-MS/MS) ( 52 ), or capillary zone electrophoresis (CE) ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic methods, such as LC–MS , LC–MS/MS , are the major techniques used for the detection and analysis of nisin and other bacteriocins in bacterium media or food matrices . These methods are precise and useful in the analysis when characterization and identification of bacteriocin is performed.…”
Section: Introductionmentioning
confidence: 99%